Surface characterization, electrochromic and capacitive properties of poly (N-(4-(4-thieno [3,2-b]thiophen-3-yl-phenyl) phenyl)-N-phenylbenzenamine) film - EROĞLU, MEHMET SAYIP (ELSEVIER SCI LTD, 2020)
N-(4-(4-thieno [3,2-b]thiophen-3-yl-phenyl)phenye-N-phenylbenzenamine (TTpTPA), synthesized by Suzuki cross-coupling reaction, was electropolymerized in DCM/CAN (4/1 v/v) mixture, containing 0.1 M Bu4NPF6. Charge storage property of the polymer, investigated by electrochemical impedance spectroscopy measurements at different potentials, suggested that the highest capacitance value could be obtained at its anodic peak potentials. Double layer and low-frequency capacitances were found to be C-DL = 369 Fg(-1) and C LF = 447 Fg(-1) at E-DC = 1.23 V. These values are in good agreement with the results obtained from equivalent circuit model. Electrochromic properties of the corresponding polymer, PolyTTpTPA, were investigated by spectroelectrochemical measurements, which indicated that while the polymer had a gold-orange color in its neutral state with an absorption maximum of 378 nm, it became blue in its oxidized state with an absorption maximum of 850 nm. Chronocoulometric measurement of the film exhibited a residence time of 10 s, indicating a fast response time and stable photoelectrochemical behavior, which are the most important parameters for electrochromic applications. In addition, hydrophobic property of the film, having a contact angle measurement of 115 degrees, is a good advantage for electronic applications for outdoor and wet areas. This work demonstrates that reversible capacitive current property and porous structure of PolyTTpTPA, supported by SEM and AFM images, make it a good candidate for electrochromic and capacitor devices.
Keywords: Thienothiophene; Triphenylamine; Electropolymerization; Cyclic voltammetry; Electrochromic; EIS; Capacitance; SUPERCAPACITOR DEVICES; POLYTHIOPHENE FILMS; CONDUCTING-POLYMER; POLYANILINE FILMS; TRIPHENYLAMINE; ELECTROPOLYMERIZATION; THIOPHENE; ELECTRODES; IMPEDANCE; GRAPHENE